Catalytic conversion of cellulose for efficient ethylene glycol production and insights into the reaction pathways. Issue 81 (16th August 2016) - Zhang, Kai; Wu, Shubin; Yang, He; Yin, Huimin; Li, Gang
Abstract : A highly active mixed catalyst consisting of PTA and Ru/AC was used for one-pot hydrothermal conversion of cellulose for EG production, and insights into the reaction pathways were obtained with the aid of cellobiose as a model compound. Abstract : As promising and environmentally friendly catalysts, tungsten-containing heteropoly acids combined with supported noble metals were used for one-pot hydrothermal conversion of cellulose into polyols in the presence of pressurized hydrogen. The microcrystalline cellulose was completely converted over a mixed catalyst consisting of a low concentration of phosphotungstic acid (PTA) (0.03 wt%) and Ru/activated carbon (Ru/AC) via an one-pot hydrothermal reaction, with an ethylene glycol (EG) yield of up to 53.1% under optimal conditions. The catalytic activity of the mixed catalyst gradually decreased with increasing reaction runs, which could be mainly ascribed to the aggregation of Ru/AC particles, and to the coverage of the active sites of Ru due to the deposition of organic materials. Cellobiose was used as a model feedstock for a comparative study on the reaction pathways of the conversion of cellulose, and the results revealed that catalytic conversion of cellobiose consisted of at least three important parallel reactions under the present hydrothermal conditions, which were also most likely involved during the catalytic conversion of cellulose for EG production. Effective control of these reactions would be helpful to further maximize the EG yield during the catalytic conversion of cellulose.